LA EVOLUCIÓN DE LA EDUCACIÓN AMBIENTAL EN COSTA RICA - Solano Muñoz, Edgar (Universidad de Costa Rica, 2006)
The article it represents a historical pursuit of the evolution that has suffered theenvironmental education and of how this has moved from the years 80 of the XXcentury toward the tendencies related with the sustainable development. Thetransformation is analyzed that suffers the nature notion “object”, modeled from theXVIII century in the Emilio of Rousseau, and like you ends up becoming themodern conception of ecosystems.